Instruction Via Satellite Television: An Exploratory Analysis of Teacher Effectiveness - Bruce O. Barker; Kenneth R. Patrick (Journal of Research in Rural Education, 1988)
Growing interest in the concept ofinteractive satellite instruction is being expressed by state and national education leaders and education policy makers in the United States.Congressionalpassage of19 million funding for the Star Schools program is one recent example [1]. Legislative approval to establish statewide satellite instructional systems in North Carolina, Kentucky, and Missouri are other examples [4].